Graphene composite material and its preparation method

By combining graphene oxide, magnetic particle powder and single-wall carbon nanotubes, a sponge framework structure is formed, and acetylene gas is introduced during the preparation process, the problem of low absorption efficiency of graphene materials is solved, and a graphene composite material with high absorption efficiency and structural stability is achieved.

CN119822362BActive Publication Date: 2025-06-03CHERY AUTOMOBILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510309235.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-06-03
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing graphene materials have poor impedance matching in electromagnetic wave absorption, resulting in low absorption efficiency.

Method used

By combining graphene oxide, magnetic particle powder and single-wall carbon nanotubes, a sponge framework structure is formed, and acetylene gas is introduced during the preparation process to deposit an amorphous carbon layer to enhance the stability and absorbance of the material.

Benefits of technology

It improves the absorption efficiency and structural stability of graphene composite materials, enhances dielectric loss and hysteresis loss, extends the absorption path of electromagnetic waves, and thus improves the overall absorption capacity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822362B_ABST
    Figure CN119822362B_ABST
Patent Text Reader

Abstract

The present application discloses a graphene composite material and a preparation method thereof, belonging to the technical field of wave-absorbing materials. In the preparation method of the graphene composite material provided by the present application, graphene and single-walled carbon nanotubes form a sponge skeleton material, and magnetic particle powders are filled in the gaps of the skeleton. The skeleton composed of graphene and carbon nanotubes is more stable, and the magnetic particle powders are also beneficial to improving the hysteresis loss of the material. Moreover, the sponge-like substrate has a large number of pore structures, which is beneficial to extending the absorption path of electromagnetic waves and improving the electromagnetic wave absorption efficiency, thereby enhancing the absorption capacity of the material. After acetylene pyrolysis, it is deposited in the surface gaps of the material, and the surface defects and uncovered pores of graphene are repaired or coated by an amorphous carbon layer. The amorphous carbon layer can effectively prevent the skeleton structure from directly contacting with water or other corrosive substances and maintain the stability of the internal structure. It can be seen that the graphene composite material prepared by this method has both high structural stability and high wave-absorbing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of microwave absorbing materials, and particularly to a graphene composite material and a preparation method thereof. Background Art

[0002] In recent years, with the development of electronic devices such as mobile phones and computers, the electromagnetic interference problem caused by electromagnetic waves has become increasingly serious. The application of microwave absorbing materials can effectively alleviate electromagnetic interference, and its absorption mechanism is to convert the energy of incident waves into other forms of energy, such as heat energy. This energy conversion is caused by the magnetic loss and dielectric loss of the microwave absorbing materials. Therefore, to improve the electromagnetic absorption ability, it is necessary to achieve good impedance matching between magnetic loss and dielectric loss. As a new type of carbon-based material, graphene has been widely studied due to its unique advantages of high dielectric loss and low density. However, as a non-magnetic material, the microwave absorption performance of graphene is mainly attributed to its dielectric loss, resulting in poor impedance matching. Therefore, how to improve the microwave absorption efficiency of graphene matrix materials is an urgent problem to be solved. Summary of the Invention

[0003] The embodiments of this application provide a graphene composite material and a preparation method thereof. The graphene composite material has both high structural stability and high microwave absorption efficiency. The technical solution is as follows:

[0004] On the one hand, a preparation method of a graphene composite material is provided, and the preparation method includes:

[0005] Preparing a graphene oxide dispersion;

[0006] Adding magnetic particle powder and single-walled carbon nanotubes into the graphene oxide dispersion to obtain a first mixed solution;

[0007] Concentrating and freeze-setting the first mixed solution to obtain a first composite material;

[0008] Annealing the first composite material to obtain a second composite material;

[0009] Placing the second composite material in a carbonization furnace, heating for a first period of time in a nitrogen atmosphere, cooling and then transferring it to a rotary furnace, and the temperature of the rotary furnace is 500 - 560 °C;

[0010] Introducing acetylene gas into the rotary furnace, and after reacting for a second period of time, a graphene composite material is obtained.

[0011] In a possible implementation manner, the preparation of the graphene oxide dispersion includes:

[0012] Mixing graphite powder, sodium nitrate and concentrated sulfuric acid, and stirring in an ice bath to obtain a second mixed solution;

[0013] Add potassium permanganate to the second mixed solution to obtain a third mixed solution;

[0014] Drop deionized water and hydrogen peroxide into the third mixed solution and wash until the pH is 4 - 7 to obtain the graphene oxide dispersion.

[0015] In another possible implementation, the mass of the graphite powder is 100 - 500 g, the mass of the sodium nitrate is 50 - 200 g, the volume of the concentrated sulfuric acid is 1 - 3 L, the mass of the potassium permanganate is 300 - 600 g, the volume of the deionized water is 15 - 25 L, and the volume of the hydrogen peroxide is 2 - 8 L.

[0016] In another possible implementation, the concentration and freeze - shaping of the first mixed solution to obtain the first composite material include:

[0017] Concentrate the first mixed solution, and the viscosity after concentration is 3000 - 10000 mPa·S;

[0018] Transfer the concentrated first mixed solution to a preset plate mold and perform freeze - shaping with liquid nitrogen;

[0019] Use the freeze - drying process to remove the moisture in the freeze - shaped first mixed solution to obtain the first composite material.

[0020] In another possible implementation, the process conditions of the freeze - drying process are: the vacuum degree is 40 - 100 Pa, the freezing temperature is - 80 - - 50 °C, and the cooling rate is 5 - 15 °C / min.

[0021] In another possible implementation, the process conditions of the annealing treatment are: the annealing temperature is 400 - 800 °C, the holding time is 4 - 8 h, and the cooling rate is 5 - 15 °C / min.

[0022] In another possible implementation, the mass of the magnetic particle powder is 10 - 100 g, the mass of the single - wall carbon nanotube is 8 - 50 g, and the volume of the graphene oxide dispersion is 2 - 5 L.

[0023] In another possible implementation, the magnetic particle powder includes at least one of nano - iron powder and magnetite powder.

[0024] In another possible implementation, the heating temperature in the carbonization furnace is 500 - 650 °C, and the first duration is 4 - 8 h;

[0025] The flow rate of the acetylene gas is 1 - 5 L / min, and the second duration is 6 - 10 h.

[0026] On the other hand, a graphene composite material is provided, and the graphene composite material is prepared by using the preparation method described in any one of the above.

[0027] The embodiment of the present application provides a preparation method of a graphene composite material. This method uses graphene oxide, magnetic particle powder, and single-walled carbon nanotubes to prepare the composite material, and acetylene gas is introduced during the preparation process. Among them, graphene and single-walled carbon nanotubes form a sponge skeleton material, and the magnetic particle powder is filled in the gaps of the skeleton. Compared with a single skeleton, the skeleton composed of graphene and carbon nanotubes is more stable, and at the same time, graphene and carbon nanotubes construct a planar and vertical conductive network, which can accelerate the migration of carriers and effectively enhance the dielectric loss of the material. The magnetic particle powder is also beneficial to improving the hysteresis loss of the material, and the sponge-like substrate has a large number of pore structures, which is beneficial to extending the absorption path of electromagnetic waves and improving the electromagnetic wave absorption efficiency, thereby enhancing the absorption capacity of the material. At the same time, after acetylene cracking, it can be deposited in the surface gaps of the material, and the surface defects and uncovered pores of graphene are repaired or coated by an amorphous carbon layer. The amorphous carbon layer can effectively prevent the skeleton structure from directly contacting water or other corrosive substances and maintain the stability of the internal structure. It can be seen that the graphene composite material prepared by this method has both high structural stability and high wave absorption efficiency.

[0028] It should be understood that the above general description and the following detailed description are only exemplary and do not limit the present disclosure. Description of the Drawings

[0029] Figure 1 is a flowchart of a preparation method of a graphene composite material provided by an embodiment of the present application;

[0030] Figure 2 is a TEM morphology diagram of a graphene material prepared by a comparative example provided by an embodiment of the present application;

[0031] Figure 3 is a TEM morphology diagram of a graphene composite material prepared in Example 3 provided by an embodiment of the present application;

[0032] Figure 4 is a schematic diagram of reflectivity testing on the graphene composite materials prepared in Examples 1 - 5 and the graphene material prepared by the comparative example provided by an embodiment of the present application;

[0033] Figure 5 is a schematic diagram of the real part of the complex permittivity versus frequency for the complex permittivity testing on the graphene composite materials prepared in Examples 1 - 5 and the graphene material prepared by the comparative example provided by an embodiment of the present application;

[0034] Figure 6It is a schematic diagram showing the imaginary part of the complex dielectric constant versus frequency for the graphene composite materials prepared in Examples 1 to 5 and the graphene materials prepared in the comparative examples provided by the embodiments of the present application;

[0035] Figure 7 It is a schematic diagram showing the real part of the magnetic permeability versus frequency for the graphene composite materials prepared in Examples 1 to 5 and the graphene materials prepared in the comparative examples provided by the embodiments of the present application;

[0036] Figure 8 It is a schematic diagram showing the imaginary part of the magnetic permeability versus frequency for the graphene composite materials prepared in Examples 1 to 5 and the graphene materials prepared in the comparative examples provided by the embodiments of the present application. Detailed implementation manners

[0037] To make the technical solutions and advantages of the present application clearer, the embodiments of the present application will be further described in detail below.

[0038] On the one hand, the embodiments of the present application provide a preparation method of a graphene composite material. Refer to Figure 1 , the preparation method includes:

[0039] Step 101: Prepare a graphene oxide dispersion.

[0040] This step can be achieved through the following steps (1) to (3), including:

[0041] (1) Mix graphite powder, sodium nitrate and concentrated sulfuric acid, and stir in an ice bath to obtain a second mixture.

[0042] Among them, the mass of the graphite powder is 100 - 500 g, the mass of sodium nitrate (NaNO 3 ) is 50 - 200 g, the concentration of the concentrated sulfuric acid is 98%, and the volume is 1 - 3 L.

[0043] The mass of the graphite powder can be 100 g, 150 g, 200 g, 250 g, 300 g, 350 g, 400 g, 450 g, 500 g, and the mass of NaNO 3 can be 50 g, 80 g, 100 g, 150 g, 200 g, and the volume of 98% concentrated sulfuric acid can be 1 L, 1.2 L, 1.5 L, 1.8 L, 2 L, 2.5 L, 3 L.

[0044] The stirring time in step (1) can be 0.5 - 2 h. For example, the stirring time is 0.5 h, 1 h, 1.5 h, 2 h. In the embodiments of the present application, only the stirring time of 1 h is taken as an example for illustration.

[0045] (2) Add potassium permanganate to the second mixed solution to obtain a third mixed solution.

[0046] Add potassium permanganate (KMnO 4 ) to the second mixed solution, and continue stirring for 1 - 3 h to obtain a third mixed solution.

[0047] Among them, the mass of KMnO 4 is 300 - 600 g. Specifically, the mass of KMnO 4 can be 300 g, 350 g, 400 g, 450 g, 500 g, 550 g, 600 g.

[0048] The stirring time in step (2) can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h. In the embodiments of the present application, only the case where the stirring time is 2 h is taken as an example for illustration.

[0049] It should be noted that after obtaining the third mixed solution, the third mixed solution can be stored at 25 - 35 °C for 20 - 40 min, and then step (3) is carried out.

[0050] Among them, the storage time can be 20 min, 25 min, 30 min, 35 min, 40 min, and the storage temperature can be 25 °C, 28 °C, 30 °C, 32 °C, 35 °C.

[0051] (3) Dropwise add deionized water and hydrogen peroxide to the third mixed solution, and wash until the pH is 4 - 7 to obtain a graphene oxide dispersion.

[0052] Among them, the volume of deionized water is 15 - 25 L, the volume of hydrogen peroxide is 2 - 8 L, and the concentration of hydrogen peroxide is 5%.

[0053] The volume of deionized water can be 15 L, 18 L, 20 L, 22 L, 25 L, and the volume of hydrogen peroxide can be 2 L, 3 L, 4 L, 5 L, 6 L, 7 L, 8 L.

[0054] Dropwise add deionized water and hydrogen peroxide to the third mixed solution, dilute the strong acid with deionized water, and initially rinse the excessive oxidant and strong acid, and then wash with deionized water and hydrochloric acid until the pH is 4 - 7 to obtain a graphene oxide dispersion.

[0055] Among them, the concentration of the graphene oxide dispersion is 0.5 - 2 mol / L. For example, the concentration of the graphene oxide dispersion is 0.5 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L. In the embodiments of the present application, only the case where the concentration of the graphene oxide dispersion is 1 mol / L is taken as an example for illustration.

[0056] The pH of the graphene oxide dispersion can be 4, 5, 6, or 7. In the embodiments of the present application, only the case where the pH of the graphene oxide dispersion is 5 is taken as an example for illustration.

[0057] During washing, first wash with deionized water, and then wash with hydrochloric acid. The concentration of hydrochloric acid is 5%.

[0058] In the embodiments of the present application, by adding strong acid / strong oxidant to fully oxidize the graphite sheets, oxygen-containing defects are generated on the graphite surface, thereby gradually increasing the graphite layer spacing until complete exfoliation to produce graphene oxide. Compared with graphene, graphene oxide has more polar functional groups and can form a uniform dispersion in polar solvents such as water or ethanol, so as to facilitate the subsequent formation of graphene aerogel.

[0059] Step 102: Add magnetic particle powder and single-walled carbon nanotubes to the graphene oxide dispersion to obtain a first mixed solution.

[0060] The mass of the magnetic particle powder is 10 - 100 g, the mass of the single-walled carbon nanotubes is 8 - 50 g, and the volume of the graphene oxide dispersion is 2 - 5 L.

[0061] Among them, the mass of the magnetic particle powder can be 10 g, 20 g, 30 g, 40 g, 50 g, 60 g, 70 g, 80 g, 90 g, 100 g, the mass of the single-walled carbon nanotubes can be 8 g, 9 g, 10 g, 15 g, 18 g, 20 g, 25 g, 30 g, 35 g, 40 g, 45 g, 50 g, and the volume of the graphene oxide dispersion can be 2 L, 2.5 L, 3 L, 3.5 L, 4 L, 4.5 L, 5 L.

[0062] Among them, the particle size of the magnetic particle powder is 50 - 200 nm. For example, the particle size of the magnetic particle powder is 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm.

[0063] The magnetic particle powder includes at least one of nano iron powder and iron 3 O 4 powder. The nano iron powder is ultrafine nano iron powder, and the Fe 3 O 4 powder is ultrafine Fe 3 O 4 powder. In the embodiments of the present application, only the case where the magnetic particle powder is ultrafine nano iron powder is taken as an example for illustration. Among them, the particle size of the ultrafine nano iron powder is 50 - 100 nm.

[0064] The diameter of the single-walled carbon nanotubes is 10 - 20 nm. For example, the length of the single-walled carbon nanotubes is 10 nm, 12 nm, 15 nm, 18 nm, 20 nm.

[0065] It should be noted that before performing step 102, the magnetic particle powder can be sequentially placed in ethanol, hydrochloric acid, and distilled water, and the impurities and oxide layer on its surface can be effectively removed by ultrasonic washing. Then, the powder is dried. That is, the magnetic particle powder used in step 102 is the dried magnetic particle powder.

[0066] Among them, the ultrasonic washing time is 10 - 20 min. For example, the ultrasonic washing time is 10 min, 12 min, 15 min, 18 min, 20 min. In the embodiment of the present application, only the ultrasonic washing time of 15 min is taken as an example for illustration.

[0067] The drying temperature is 100 - 150 °C. For example, the drying temperature is 100 °C, 110 °C, 120 °C, 130 °C, 140 °C, 150 °C. In the embodiment of the present application, only the drying temperature of 120 °C is taken as an example for illustration.

[0068] The drying time is 4 - 8 h. For example, the drying time is 4 h, 5 h, 6 h, 7 h, 8 h. In the embodiment of the present application, only the drying time of 6 h is taken as an example for illustration.

[0069] After performing step 102, the first mixed solution can be ultrasonically treated to make each component mix evenly. Among them, the ultrasonic treatment time can be 20 - 40 min. For example, the ultrasonic treatment time is 20 min, 25 min, 30 min, 35 min, 40 min. In the embodiment of the present application, only the ultrasonic treatment time of 30 min is taken as an example for illustration.

[0070] Step 103: Concentrate and freeze - shape the first mixed solution to obtain the first composite material.

[0071] This step can be realized through the following steps (1) to (3), including:

[0072] (1) Concentrate the first mixed solution, and the viscosity after concentration is 3000 - 10000 mPa·S.

[0073] The first mixed solution can be concentrated by heating, and mechanical stirring is carried out during the concentration process to ensure uniform mixing and the best concentration effect.

[0074] The viscosity after concentration can be 3000 mPa·S, 4000 mPa·S, 5000 mPa·S, 6000 mPa·S, 7000 mPa·S, 8000 mPa·S, 9000 mPa·S, 10000 mPa·S, and no specific limitation is made thereto. In the embodiment of the present application, only the viscosity after concentration of 5000 mPa·S is taken as an example for illustration.

[0075] (2) Transfer the concentrated first mixture to a preset plate mold and freeze it into shape with liquid nitrogen.

[0076] Transfer the concentrated first mixture to a preset plate mold with a thickness of 2 - 10 mm, and then quickly freeze and shape the mixture transferred to the mold with liquid nitrogen to keep its shape and structure stable.

[0077] Among them, the thickness of the mold can be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, and no specific limitation is made thereto. In the embodiment of the present application, only the case where the thickness of the mold is 5 mm is taken as an example for illustration. In addition, the shape of the mold can be set and changed as needed, and no specific limitation is made thereto.

[0078] (3) Remove the moisture in the first mixture after freeze - shaping by freeze - drying process to obtain the first composite material.

[0079] Use the freeze - drying process to further process the first mixture after freeze - shaping to remove the moisture therein, and obtain a composite material with a sponge - like structure, that is, the first composite material.

[0080] In the embodiment of the present application, the process conditions of the freeze - drying process are: the vacuum degree is 40 - 100 Pa, the freezing temperature is - 80°C to - 50°C, and the cooling rate is 5 - 15°C / min.

[0081] Among them, the vacuum degree can be 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 100 Pa, and no specific limitation is made thereto. In the embodiment of the present application, only the case where the vacuum degree is 40 Pa is taken as an example for illustration.

[0082] The freezing temperature can be - 80°C, - 75°C, - 70°C, - 65°C, - 60°C, - 55°C, - 50°C, and no specific limitation is made thereto. In the embodiment of the present application, only the case where the freezing temperature is - 80°C is taken as an example for illustration.

[0083] The cooling rate can be 5°C / min, 8°C / min, 9°C / min, 10°C / min, 12°C / min, 13°C / min, 15°C / min, and no specific limitation is made thereto. In the embodiment of the present application, only the case where the cooling rate is 10°C / min is taken as an example for illustration.

[0084] Step 104: Anneal the first composite material to obtain the second composite material.

[0085] Among them, the second composite material is an uncoated graphene aerogel composite material.

[0086] In the embodiments of the present application, the process conditions for the annealing treatment are as follows: the annealing temperature is 400~800°C, the holding time is 4~8h, and the cooling rate is 5~15°C / min.

[0087] Among them, the annealing temperature can be 400°C, 500°C, 600°C, 700°C, 800°C, and no specific limitation is made thereto. In the embodiments of the present application, only the case where the annealing temperature is 600°C is taken as an example for illustration.

[0088] The holding time can be 4h, 5h, 6h, 7h, 8h, and no specific limitation is made thereto. In the embodiments of the present application, only the case where the holding time is 6h is taken as an example for illustration.

[0089] The cooling rate can be 5°C / min, 8°C / min, 9°C / min, 10°C / min, 12°C / min, 13°C / min, 15°C / min, and no specific limitation is made thereto. In the embodiments of the present application, only the case where the cooling rate is 10°C / min is taken as an example for illustration.

[0090] Step 105: Place the second composite material in a carbonization furnace, heat it for a first duration under a nitrogen atmosphere, and transfer it to a rotary furnace after cooling. The temperature of the rotary furnace is 500~560°C.

[0091] Among them, the heating temperature in the carbonization furnace is 500~650°C, the first duration is 4~8h, and the flow rate of nitrogen is 10~20L / min.

[0092] Specifically, the heating temperature in the carbonization furnace can be 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, and no specific limitation is made thereto. In the embodiments of the present application, only the case where the heating temperature in the carbonization furnace is 580°C is taken as an example for illustration.

[0093] The temperature of the rotary furnace can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C.

[0094] It should be noted that the temperature of the rotary furnace is less than or equal to the temperature of the carbonization furnace. In the embodiments of the present application, only the case where the temperature of the rotary furnace is less than the temperature of the carbonization furnace is taken as an example for illustration.

[0095] The first duration can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, and no specific limitation is made thereto. In the embodiments of the present application, only the case where the first duration is 6h is taken as an example for illustration.

[0096] The flow rate of nitrogen can be 10 L / min, 12 L / min, 15 L / min, 18 L / min, 20 L / min, and no specific limitation is imposed thereon. In the embodiments of the present application, only the case where the flow rate of nitrogen is 15 L / min is taken as an example for illustration.

[0097] It should be noted that before introducing acetylene gas, the rotary furnace can be evacuated first, and then argon gas is introduced into the rotary furnace to purify the cavity, and then evacuated again, and then acetylene gas is introduced.

[0098] Among them, the vacuum degree in the rotary furnace can be 20 - 60 Pa. For example, the vacuum degree in the rotary furnace is 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa.

[0099] The flow rate of argon is 10 - 20 L / min. For example, the flow rate of argon can be 10 L / min, 12 L / min, 15 L / min, 18 L / min, 20 L / min, and no specific limitation is imposed thereon. In the embodiments of the present application, only the case where the flow rate of argon is 15 L / min is taken as an example for illustration.

[0100] The time for introducing argon can be set and changed as needed, and no specific limitation is imposed thereon. For example, the time for introducing argon is 5 min, 6 min, 8 min, 10 min.

[0101] Step 106: Introduce acetylene gas into the rotary furnace, and after reacting for a second duration, a graphene composite material is obtained.

[0102] Among them, the flow rate of acetylene gas is 1 - 5 L / min. For example, the flow rate of acetylene gas is 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min. In the embodiments of the present application, only the case where the flow rate of acetylene gas is 3 L / min is taken as an example for illustration.

[0103] The second duration is 6 - 10 h. For example, the second duration is 6 h, 7 h, 8 h, 9 h, 10 h. In the embodiments of the present application, only the case where the second duration is 8 h is taken as an example for illustration.

[0104] The rotary furnace can be a MOCVD (Metal-Organic Chemical Vapor Deposition) rotary furnace.

[0105] In the embodiments of the present application, graphene and single-walled carbon nanotubes form a sponge skeleton material, and magnetic particle powder is filled in the skeleton gaps. Among them, the pore size of the sponge skeleton is 50-100 nm, the particle size of the magnetic particle powder is 50-200 nm, the filling rate is 35%-50%, the diameter of the single-walled carbon nanotubes is 10-20 nm, and the outermost layer is covered by an amorphous carbon layer with a thickness of about 15 nm, which can effectively prevent the skeleton structure from directly contacting water or other corrosive substances, maintain the stability of the internal structure, and enhance the durability and corrosion resistance of the material. In addition, the graphene and carbon nanotube skeleton is more stable than a single skeleton structure. The coverage or mixing of a single graphene sheet layer may cause the sheet layer to slip off or even interface failure under the action of mechanical force. Moreover, graphene and carbon nanotubes simultaneously construct a planar and vertical conductive network, which can accelerate the migration of carriers, effectively enhance the dielectric loss of the material, and the fibrous structure of carbon nanotubes can also improve the diversification of the wave absorption mode of the material. In addition, the synergistic effect brought by the nano-scale magnetic particle powder is beneficial to improving the hysteresis loss of the material, and the nano-structure also improves the bonding stability and dispersibility between materials; the porous sponge-like substrate has a large number of pore structures, which is beneficial to extending the electromagnetic wave absorption path, improving the electromagnetic wave absorption efficiency, and enhancing the absorption ability of the material.

[0106] On the other hand, a graphene composite material is provided, and the graphene composite material is prepared by the above-mentioned preparation method.

[0107] The technical solutions of the present application will be described in detail below through specific embodiments.

[0108] In the following specific embodiments, the operations involved without indicating conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer.

[0109] Example 1

[0110] Example 1 provides a graphene composite material, which is obtained by the following preparation method:

[0111] (1) Prepare a graphene oxide dispersion: Mix 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and wash repeatedly with deionized water and 5% hydrochloric acid to obtain a graphene oxide dispersion. The concentration of the graphene oxide dispersion is 1 mol / L and the pH is 5.

[0112] (2) Place 10 g of ultrafine nano iron powder successively in ethanol, hydrochloric acid, and distilled water, and ultrasonically wash for 15 min to remove impurities and oxide layers on its surface. After completion of the washing, dry the powder at 120 °C for 6 h. Subsequently, add the dried ultrafine nano iron powder and 9 g of single-walled carbon nanotubes together to 3 L of graphene oxide dispersion liquid.

[0113] (3) Ultrasonically treat for 30 min, then perform mechanical stirring, and at the same time of stirring, perform concentration operation to make the viscosity of the mixed liquid reach 5000 mPa·S.

[0114] (4) Transfer the concentrated mixed liquid to a specific plate mold, and use liquid nitrogen to quickly freeze and shape the mixed liquid in the mold.

[0115] (5) Place the material after freeze shaping into a freeze dryer, with a freezing temperature of -80 °C, a vacuum degree of 40 Pa, a cooling rate of 10 °C / min, keep the temperature and pressure constant for 48 h, and then take out the composite material. At this time, the internal moisture of the composite material is completely removed.

[0116] (6) Anneal the composite material, with an annealing temperature of 600 °C, a heat preservation time of 6 h, and a cooling rate of 10 °C / min. After annealing treatment, an uncoated graphene aerogel composite material is obtained.

[0117] (7) Place the graphene aerogel composite material into a carbonization furnace, evacuate to a vacuum degree of 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, with a nitrogen gas flow rate of 15 L / min. After cooling, transfer it into a MOCVD furnace, and the temperature of the MOCVD furnace is 540 °C.

[0118] (8) The MOCVD furnace first evacuates to a vacuum degree of 40 Pa, introduces argon gas to purify the cavity, with an argon gas flow rate of 15 L / min. After 5 min, evacuate to 40 Pa, introduce acetylene gas, with a flow rate of acetylene gas of 3 L / min, and the reaction time is 8 h to obtain an amorphous carbon-coated graphene composite material.

[0119] Example 2

[0120] Example 2 provides a graphene composite material, which is obtained through the following preparation method:

[0121] (1) Prepare graphene oxide dispersion liquid: Mix 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h, and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and repeatedly wash with deionized water and 5% hydrochloric acid to obtain graphene oxide dispersion liquid. The concentration of the graphene oxide dispersion liquid is 1 mol / L, and the pH is 5.

[0122] (2) Place 20 g of ultrafine nano iron powder successively in ethanol, hydrochloric acid and distilled water, and ultrasonically wash for 15 min to remove the impurities and oxide layer on its surface. After the cleaning is completed, dry the powder at 120 °C for 6 h. Subsequently, add the dried ultrafine nano iron powder and 18 g of single-walled carbon nanotubes together to 3 L of graphene oxide dispersion.

[0123] (3) Ultrasonically treat for 30 min, then carry out mechanical stirring, and at the same time of stirring, carry out a concentration operation to make the viscosity of the mixed solution reach 5000 mPa·S.

[0124] (4) Transfer the concentrated mixed solution to a specific plate mold, and use liquid nitrogen to quickly freeze and shape the mixed solution in the mold.

[0125] (5) Place the frozen and shaped material in a freeze dryer, with a freezing temperature of -80 °C, a vacuum degree of 40 Pa, a cooling rate of 10 °C / min, keep the temperature and pressure constant for 48 h, and take out the composite material. At this time, the composite material completely removes the internal moisture.

[0126] (6) Anneal the composite material, with an annealing temperature of 600 °C, a holding time of 6 h, and a cooling rate of 10 °C / min. After the annealing treatment, an uncoated graphene aerogel composite material is obtained.

[0127] (7) Place the graphene aerogel composite material in a carbonization furnace, evacuate to a vacuum degree of 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, with a nitrogen flow rate of 15 L / min. After cooling, transfer it to a MOCVD furnace, and the temperature of the MOCVD furnace is 540 °C.

[0128] (8) First evacuate the MOCVD furnace to a vacuum degree of 4 Pa, introduce argon gas to purify the cavity, with an argon flow rate of 15 L / min. After 5 min, evacuate to 40 Pa, introduce acetylene gas, with an acetylene gas flow rate of 3 L / min, and the reaction time is 8 h to obtain an amorphous carbon-coated graphene composite material.

[0129] Example 3

[0130] Example 3 provides a graphene composite material, which is obtained by the following preparation method:

[0131] (1) Prepare graphene oxide dispersion: Mix 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and repeatedly wash with deionized water and 5% hydrochloric acid to obtain graphene oxide dispersion. The concentration of the graphene oxide dispersion is 1 mol / L and the pH is 5.

[0132] (2) Place 50 g of ultrafine nano iron powder in ethanol, hydrochloric acid, and distilled water in sequence, and ultrasonically wash for 15 min to remove impurities and oxide layers on its surface. After cleaning, dry the powder at 120 °C for 6 h. Subsequently, add the dried ultrafine nano iron powder and 36 g of single-walled carbon nanotubes into 3 L of graphene oxide dispersion liquid.

[0133] (3) Ultrasonically treat for 30 min, then carry out mechanical stirring, and perform concentration operation while stirring to make the viscosity of the mixed liquid reach 5000 mPa·S.

[0134] (4) Transfer the concentrated mixed liquid to a specific plate mold, and use liquid nitrogen to quickly freeze and shape the mixed liquid in the mold.

[0135] (5) Place the frozen and shaped material into a freeze dryer, with a freezing temperature of -80 °C, a vacuum degree of 40 Pa, a cooling rate of 10 °C / min, keep the temperature and pressure constant for 48 h, and then take out the composite material. At this time, the internal moisture of the composite material is completely removed.

[0136] (6) Anneal the composite material, with an annealing temperature of 600 °C, a heat preservation time of 6 h, and a cooling rate of 10 °C / min. After annealing treatment, an uncoated graphene aerogel composite material is obtained.

[0137] (7) Place the graphene aerogel composite material into a carbonization furnace, evacuate to a vacuum degree of 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, with a nitrogen flow rate of 15 L / min. After cooling, transfer it to an MOCVD furnace, and the temperature of the MOCVD furnace is 540 °C.

[0138] (8) First, evacuate the MOCVD furnace to a vacuum degree of 4 Pa, introduce argon gas to purify the cavity, with an argon flow rate of 15 L / min. After 5 min, evacuate to 40 Pa, introduce acetylene gas, with an acetylene gas flow rate of 3 L / min, and the reaction time is 8 h to obtain an amorphous carbon-coated graphene composite material.

[0139] Example 4

[0140] Example 4 provides a graphene composite material, which is obtained through the following preparation method:

[0141] (1) Prepare graphene oxide dispersion liquid: Mix 150 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h, and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and repeatedly wash with deionized water and 5% hydrochloric acid to obtain graphene oxide dispersion liquid. The concentration of the graphene oxide dispersion liquid is 1 mol / L, and the pH is 5.

[0142] (2) Place 50 g of ultrafine nanometer iron powder successively in ethanol, hydrochloric acid, and distilled water, and ultrasonically wash for 15 min to remove the impurities and oxide layer on its surface. After the cleaning is completed, dry the powder at 120 °C for 6 h. Subsequently, add the dried ultrafine nanometer iron powder and 18 g of single-walled carbon nanotubes together to 3 L of graphene oxide dispersion liquid.

[0143] (3) Ultrasonically treat for 30 min, and then perform mechanical stirring. While stirring, perform a concentration operation to make the viscosity of the mixed liquid reach 5000 mPa·S.

[0144] (4) Transfer the concentrated mixed liquid to a specific plate mold, and use liquid nitrogen to quickly freeze and shape the mixed liquid in the mold.

[0145] (5) Place the frozen and shaped material into a freeze dryer. The freezing temperature is -80 °C, the vacuum degree is 40 Pa, the cooling rate is 10 °C / min, keep the temperature and pressure constant for 48 h, and then take out the composite material. At this time, the internal moisture of the composite material is completely removed.

[0146] (6) Perform annealing treatment on the composite material. The annealing temperature is 600 °C, the heat preservation time is 6 h, and the cooling rate is 10 °C / min. After the annealing treatment, an uncoated graphene aerogel composite material is obtained.

[0147] (7) Place the graphene aerogel composite material into a carbonization furnace, evacuate to a vacuum degree of 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, the nitrogen gas flow rate is 15 L / min, and after cooling, transfer it to an MOCVD furnace. The temperature of the MOCVD furnace is 540 °C.

[0148] (8) First, evacuate the MOCVD furnace to a vacuum degree of 4 Pa, introduce argon gas to purify the cavity, the argon gas flow rate is 15 L / min, after 5 min, evacuate to 40 Pa, introduce acetylene gas, the flow rate of the acetylene gas is 3 L / min, and the reaction time is 8 h to obtain an amorphous carbon-coated graphene composite material.

[0149] Example 5

[0150] Example 5 provides a graphene composite material, which is obtained through the following preparation method:

[0151] (1) Prepare graphene oxide dispersion liquid: Mix 150 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h, and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and repeatedly wash with deionized water and 5% hydrochloric acid to obtain graphene oxide dispersion liquid. The concentration of the graphene oxide dispersion liquid is 1 mol / L, and the pH is 5.

[0152] (2) Place 100 g of ultrafine nanometer iron powder successively in ethanol, hydrochloric acid, and distilled water, and ultrasonically wash for 15 min to remove the impurities and oxide layer on its surface. After the cleaning is completed, dry the powder at 120 °C for 6 h. Subsequently, add the dried ultrafine nanometer iron powder and 18 g of single-walled carbon nanotubes together into 3 L of graphene oxide dispersion.

[0153] (3) Ultrasonically treat for 30 min, and then perform mechanical stirring. While stirring, perform a concentration operation to make the viscosity of the mixed solution reach 5000 mPa·S.

[0154] (4) Transfer the concentrated mixed solution to a specific plate mold, and use liquid nitrogen to quickly freeze and shape the mixed solution in the mold.

[0155] (5) Place the frozen and shaped material in a freeze dryer. The freezing temperature is -80 °C, the vacuum degree is 40 Pa, the cooling rate is 10 °C / min, and keep the temperature and pressure constant for 48 h, then take out the composite material. At this time, the internal moisture of the composite material is completely removed.

[0156] (6) Anneal the composite material. The annealing temperature is 600 °C, the heat preservation time is 6 h, and the cooling rate is 10 °C / min. After the annealing treatment, an uncoated graphene aerogel composite material is obtained.

[0157] (7) Place the graphene aerogel composite material in a carbonization furnace, evacuate the vacuum degree to 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, the nitrogen gas flow rate is 15 L / min. After cooling, transfer it to a MOCVD furnace, and the temperature of the MOCVD furnace is 540 °C.

[0158] (8) First, evacuate the vacuum degree of the MOCVD furnace to 4 Pa, introduce argon gas to purify the cavity, the argon gas flow rate is 15 L / min. After 5 min, evacuate the vacuum to 40 Pa, introduce acetylene gas, the flow rate of the acetylene gas is 3 L / min, and the reaction time is 8 h to obtain an amorphous carbon-coated graphene composite material.

[0159] Comparative Example

[0160] The comparative example provides a graphene material, which is obtained by the following preparation method:

[0161] (1) Prepare graphene oxide dispersion: Mix 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid, and stir in an ice bath for 1 h. After adding 500 g of potassium permanganate, stir for another 2 h, and store at 30 °C for 0.5 h. Dropwise add 20 L of deionized water and 5 L of 5% hydrogen peroxide, and repeatedly wash with deionized water and 5% hydrochloric acid to obtain graphene oxide dispersion. The concentration of the graphene oxide dispersion is 1 mol / L, and the pH is 5.

[0162] (2) Ultrasonically treat the 3L graphene oxide dispersion for 30 min, then carry out mechanical stirring, and perform concentration operation while stirring to make the viscosity of the mixed solution reach 5000 mPa·S.

[0163] (3) Transfer the concentrated mixed solution to a specific plate mold, and quickly freeze and shape the mixed solution in the mold using liquid nitrogen.

[0164] (4) Place the frozen and shaped material into a freeze dryer. The freezing temperature is -80 °C, the vacuum degree is 40 Pa, the cooling rate is 10 °C / min, keep the temperature and pressure constant for 48 h and then take out the material. At this time, the internal moisture of the material is completely removed.

[0165] (5) Anneal the material. The annealing temperature is 600 °C, the heat preservation time is 6 h, and the cooling rate is 10 °C / min.

[0166] (6) Place the annealed material into a carbonization furnace, evacuate the vacuum degree to 40 Pa, heat at 580 °C for 6 h under a nitrogen atmosphere, the nitrogen gas flow rate is 15 L / min, transfer it to a MOCVD furnace after cooling, and the temperature of the MOCVD furnace is 540 °C.

[0167] (7) First evacuate the MOCVD furnace to a vacuum degree of 4 Pa, introduce argon gas to purify the cavity, the argon gas flow rate is 15 L / min, evacuate to 40 Pa after 5 min, introduce acetylene gas, the flow rate of the acetylene gas is 3 L / min, and the reaction time is 8 h to obtain the graphene material.

[0168] It should be noted that, compared with Example 1, the quality of the magnetic particle powder and single-walled carbon nanotubes is improved in Example 2. Compared with Example 2, the quality of the magnetic particle powder and single-walled carbon nanotubes is improved in Example 3. Compared with Example 3, the quality of the graphite powder and single-walled carbon nanotubes is reduced in Example 4. Compared with Example 4, the quality of the magnetic particle powder is improved in Example 5. Compared with Examples 1 - 5, only graphene oxide dispersion is added in the comparative example, and magnetic particle powder and single-walled carbon nanotubes are not added.

[0169] See Figure 2 and Figure 3 Figure 2 is the TEM (Transmission Electron Microscope) morphology diagram of the graphene material prepared in the comparative example, Figure 3 is the TEM morphology diagram of the graphene composite material prepared in Example 3. It can be seen from Figure 2 and Figure 3 that: single graphene is in a sheet structure. After graphene is compounded with single-walled carbon nanotubes and magnetic particle powder, a sponge-like framework structure is formed, the magnetic particle powder is filled in the framework gaps, and the outermost layer is covered by an amorphous carbon layer.

[0170] Application Example

[0171] The complex permittivity and permeability of the material in the frequency band of 2 GHz to 18 GHz are tested according to ASTM D7449 / D7449M-22a "Standard Test Method for Measuring the Complex Relative Permittivity and Relative Permeability of Solid Materials at Microwave Frequencies Using Coaxial Air Lines". The sample size is a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3.04 mm, and the material thickness is 2 mm to 3 mm.

[0172] The reflectivity of the material in the frequency band of 2 GHz to 18 GHz is tested according to GJB2038A-2011 "Test Method for Reflectivity of Radar Absorbing Materials". The sample size is 300 mm × 300 mm × 5 mm.

[0173] The reflectivity, complex permittivity and relative permeability of the materials provided in Examples 1 to 5 and the comparative example are tested. The test results are shown in Figures 4 to 8 . From Figures 4 to 8 it can be seen that: The reflectivity of the graphene composite material prepared in Example 5 is less than -5 dB in the range of 3 to 18 GHz, and it has the best wave absorption performance. This is because the complex permittivity of the graphene composite material prepared in this example is the lowest and the permeability is the highest, which most conforms to the impedance matching principle. Therefore, it has the best wave absorption performance. The graphene composite material prepared in Example 3 has good wave absorption performance at low frequencies. This is because the complex permittivity of the graphene composite material in this example is the highest, which is beneficial to the shift of the absorption peak to low frequencies. The performance of the comparative example is the worst because the content of the dielectric loss type material in the comparative example is the lowest and it does not contain magnetic loss type materials.

[0174] The above description is only for the convenience of those skilled in the art to understand the technical solution of the present application, and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a graphene composite material, characterized in that: The preparation method comprises: preparing a graphene oxide dispersion; Adding magnetic particle powder and single-walled carbon nanotubes into the graphene oxide dispersion to obtain a first mixed solution; Concentrating and freezing the first mixed solution to obtain a first composite material; annealing the first composite material to obtain a second composite material; The second composite material is placed in a carbonization furnace, heated for a first time under a nitrogen atmosphere, and transferred to a rotary kiln after cooling, wherein the temperature of the rotary kiln is 500-560° C.; Acetylene gas is introduced into the rotary kiln, and after reacting for a second time period, a graphene composite material is obtained.

2. The preparation method according to claim 1, characterized in that: The method for preparing the graphene oxide dispersion comprises: Mixing graphite powder, sodium nitrate and concentrated sulfuric acid, and stirring in an ice bath to obtain a second mixed solution; adding potassium permanganate to the second mixed solution to obtain a third mixed solution; Deionized water and hydrogen peroxide are added dropwise to the third mixed solution, and the mixture is washed until the pH value is 4 to 7 to obtain the graphene oxide dispersion.

3. The preparation method according to claim 2, characterized in that: The mass of the graphite powder is 100-500 g, the mass of the sodium nitrate is 50-200 g, the volume of the concentrated sulfuric acid is 1-3 L, the mass of the potassium permanganate is 300-600 g, the volume of the deionized water is 15-25 L, and the volume of the hydrogen peroxide is 2-8 L.

4. The preparation method according to claim 1, characterized in that: The first mixed solution is concentrated and frozen to obtain a first composite material, comprising: Concentrating the first mixed solution, wherein the viscosity after concentration is 3000-10000 mPa·S; The concentrated first mixed liquid is transferred to a preset plate mold and frozen and formed by liquid nitrogen; The first composite material is obtained by removing water from the first mixed solution after freeze-setting using a freeze-drying process.

5. The preparation method according to claim 4, characterized in that: The process conditions of the freeze-drying process are: vacuum degree of 40~100Pa, freezing temperature of -80~-50°C, and cooling rate of 5~15°C / min.

6. The preparation method according to claim 1, characterized in that: The process conditions of the annealing treatment are: annealing temperature is 400-800°C, holding time is 4-8h, and cooling rate is 5-15°C / min.

7. The preparation method according to claim 1, characterized in that: The mass of the magnetic particle powder is 10-100 g, the mass of the single-walled carbon nanotube is 8-50 g, and the volume of the graphene oxide dispersion is 2-5 L.

8. The preparation method according to claim 1, characterized in that: The magnetic particle powder includes at least one of nano iron powder and ferroferric oxide powder.

9. The preparation method according to claim 1, characterized in that: The heating temperature in the carbonization furnace is 500-650° C., and the first time is 4-8 hours; The flow rate of the acetylene gas is 1-5 L / min, and the second time length is 6-10 hours.

10. A graphene composite material, characterized in that: The graphene composite material is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of graphene-carbon nanotube hybrid sponge

    AU2020102002A4

  • Preparation method for carbon nano tube / oxidized grapheme / nanometer Fe3O4 sandwich hybrid wave absorbing thin films

    CN103813699A